Producing Feminism: Television Work in the Age of Women's Liberation - Jennifer S. Clark (University of California Press, 2024)
In this archivally informed work, Jennifer S. Clark explores the multiple ways in which the feminist priorities of the 1970s were strengthened by women who labored in the American television industry. Carefully synthesizing an array of interviews and primary sources—from television network memos to programming schedules, production notes to executive meeting agendas—Clark tells the story of how women organized in the workplace to form collectives, affect production labor, and develop reform‑oriented policies and philosophies that reshaped television behind the screen. She urges us to consider how interventions, often at localized levels, can collectively shift the dynamics of media workplaces and the cultural products created therein. "A terrific model of feminist media historiography. Jennifer Clark expands our understanding of 1970s American television, the women's liberation movement, and the deep connections among gender, labor, and activism while innovating new strategies to examine the media industries." — Elana Levine, author of Her Stories: Daytime Soap Opera and US Television History "A massively important and enlightening contribution to the field, offering a nuanced treatment of industry cooperation and compromise. Clark uses rare archival findings and a wide range of cultural objects and case studies to generate fresh, bold conclusions around second-wave feminism and American television." — Annie Berke, author of Their Own Best Creations: Women Writers in Postwar Television
Keywords: 790; women in television broadcasting; history; United States; 20th century; feminism; mass media